Six Weeks of Confinement: Psychological Effects on a Sample of Children in Early Childhood and Primary Education - Giménez-Dasí, Marta; Quintanilla, Laura; Lucas-Molina, Beatriz; Sarmento-Henrique, Renata (Frontiers in Psychology, 2020)
Spain has been one of the countries most affected by the health crisis derived from COVID-19. Within this country, the city of Madrid has registered the highest number of infections and deaths. This circumstance led to the adoption of strict confinement measures for a period of 6 weeks. The objective of the present study was to investigate the psychological effects that this confinement has had on the psychological well-being of a sample of children from Madrid. A total of 167 families with children aged 3, 6, and 10 years participated in this study. The parents evaluated the children through the SENA (System of Evaluation of Children and Adolescents) scale in the month of February and refilled part of the same scale after the children had spent between 4 and weeks confined. The comparison between the two measures showed no change among the 3-year-old children. However, change was observed among the 6 to10-year-olds.Children in Primary Education obtained lower scores in dimensions related to selfregulation (emotional, attentional and behavioral) and in willingness to study. The results are discussed in light of the situation experienced between the months of March and May 2020.